Authenticating Hadith Through the Irfani Method: An Effort in Epistemic Decolonization and the Contribution of Hadith Studies to the SDGs - Yuliana Nurul Islami; Dariyanto; Itsna Rusydiana; Binti Mar’atus Sholihah; Hari Widyasmoro (Profetika: Jurnal Studi Islam, 2026)
Objective: This article examines the application of the Irfānī method in Hadith authentication as a strategy for epistemic decolonization, aiming to develop a more inclusive, spiritually grounded, and socially responsive approach to understanding Islamic teachings while demonstrating its contribution to advancing the Sustainable Development Goals (SDGs). Theoretical framework: The study is grounded in the theory of epistemic decolonization, drawing on Muhammad Rofiq Muzakkir’s perspective to critique the dominance of Western epistemological paradigms in Islamic scholarship and to emphasize the legitimacy of indigenous Islamic epistemologies, particularly the Irfānī tradition, which integrates spiritual intuition with ethical reasoning. Literature review: Previous studies on Hadith authentication predominantly emphasize textual criticism (naqli) and rational analysis ('aqli), whereas limited attention has been given to the spiritual and metaphysical dimensions of Hadith interpretation. Existing scholarship therefore reveals a significant gap concerning the integration of experiential spirituality into contemporary Hadith studies. Method: This research employs a qualitative library research approach by examining classical and contemporary literature on Hadith studies, Islamic epistemology, Irfānī thought, and decolonial theory through descriptive and interpretive analysis. Results: The findings demonstrate that the Irfānī method complements conventional Hadith authentication by incorporating spiritual experience, moral intuition, and ethical reflection without undermining established scholarly standards. This integrative approach strengthens interpretations promoting justice, compassion, social equality, environmental responsibility, and peaceful coexistence, thereby supporting several SDGs. Implications: The study provides an alternative epistemological framework for Islamic scholarship, encouraging educational institutions and researchers to embrace epistemic plurality while producing religious knowledge that is contextually relevant and socially transformative. Novelty: The principal contribution of this research is the integration of Irfānī spirituality into Hadith authentication within an epistemic decolonization framework, offering a holistic model that connects authentic Islamic knowledge production with contemporary global sustainability agendas and ethical development.